Ranges, temporal trend, and determinants of novel obesity indices in middle-aged and older Chinese population: insights from a nationally representative and longitudinal study - Huang, Liufang; Zhou, Yifan; Abuduxukuer, Kaiweisa; Wang, Chuchu; Hou, Ya’nan; Shi, Wenming; Luo, Jianfeng; Wei, Jin; Yue, Yuhang (Frontiers in Public Health, 2025)
BackgroundTraditional obesity assessment using body mass index (BMI) fails to adequately capture fat distribution, particularly central obesity, which is closely linked to metabolic dysfunction and obesity-related complications. Alternative obesity indices that better reflecting fat distribution and body composition have shown promise, yet large-scale population-based data remain limited. This study evaluates the ranges, temporal trends, and associated factors of novel obesity indexes in a nationally representative cohort of middle-aged and older Chinese adults.MethodsUsing data from the China Health and Retirement Longitudinal Study (CHARLS), we analyzed 17,708 adults in 2011 and followed 5,078 participants over 5 years nationally. Six obesity indexes: waist-to-height ratio (WHtR), lipid accumulation product (LAP), visceral adiposity index (VAI), body shape index (ABSI), Chinese visceral adiposity index (CVAI), and weight-adjusted waist index (WWI), were evaluated for ranges, temporal trends, and associated factors using logistic regression and generalized estimating equations (GEE). Associated factors included demographic, socioeconomic, lifestyle, and medical variables.ResultsThe national ranges were as follows: VAI (−1.805 to 6.615), ABSI (0.071 to 0.095), WHtR (0.462 to 0.622), CVAI (48.993 to 147.057), WWI (10.264 to 12.144), and LAP (−3.158 to 80.818). Significant associated factors were grouped into demographic (age, sex, urban/rural residence), medical (diabetes, and hypertension), and lifestyle factors (smoking, and drinking), with varying impacts across indexes. Over the five-year period, WHtR, CVAI, and LAP increased significantly (β = 0.00489, β = 4.51607, β = 6.37441; all p < 0.001), while ABSI decreased (β = −0.00048, p < 0.001). Interaction effects showed that diabetic participants experienced reductions in VAI, WHtR, CVAI, and LAP, indication a time-dependent change. In contrast, chronic kidney disease (CKD) and hypertension had stable effects on obesity indices, with no significant changes over time.ConclusionThis study provides nationally representative baseline ranges, temporal changes and influencing factors of novel obesity indexes among middle-aged and older Chinese adults. These findings underscore the potential of these obesity indices to guide clinical interventions aimed at controlling and preventing obesity-related health issues.